SISTEM KODE PADA KOMIK CERITA RAKYAT TORAJA KAJIAN SEMIOTIKA ROLAND BARTHES - Pali, Arnovlin Evelin; AJ, Andi Agussalim; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the form of code contained in Toraja folklore comics using Roland Barthes' semiotic theory. The type of research used is descriptive qualitative. The results of the study state that there are five code systems in Toraja folklore comics. The gnomic code states several cultural codes found in the Toraja tribe, the hermeneutic code states the problem solving performed by the characters in the story, the semik code states that the characters in comics give masculine attitudes in dealing with problems, the symbolic code states problem solving according to their respective cultures, while the pro-aetic code states attitudes that imply human behavior, both positive and negative attitudes.